2018
DOI: 10.1016/j.dib.2018.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Data on fluoride concentration and health risk assessment of drinking water in Khorasan Razavi province, Iran

Abstract: While fluoride (F) is an essential anion to keep the human body healthy, high F intake could lead to serious health problems. The monitoring of F in drinking water as the main route of F intake, is a key factor in preventing its negative health consequences. Here, we present the F levels in drinking water distribution networks of Khorasan Razavi province in Iran which collected during 2016–2017. The non-cancer human risk attributed to F in municipal and rural regions, also, estimated by calculating the chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Table 6 shows that all HQ values of the PTEs were less than one for adults and children. Consequently, evaluating the human health risk associated with all detected trace elements revealed that the HQ values exhibit a satisfactory degree of non-carcinogenic adverse health risk (Turdi and Yang 2016;Ghaderpoori et al 2018). nevertheless, regular monitoring is still required since unexpected contamination may occur.…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…Table 6 shows that all HQ values of the PTEs were less than one for adults and children. Consequently, evaluating the human health risk associated with all detected trace elements revealed that the HQ values exhibit a satisfactory degree of non-carcinogenic adverse health risk (Turdi and Yang 2016;Ghaderpoori et al 2018). nevertheless, regular monitoring is still required since unexpected contamination may occur.…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…Natural sources of fluoride occur from the erosion of fluoride-rich minerals, especially granites and volcanic rocks, and these represent the normal route of fluoride in waters (Yousefi et al, 2019). Anthropogenic activities also play an important role in the process by which fluoride is transported into waters (Mohammadi et al, 2017;Ghaderpoori et al, 2018). These activities included aluminum smelters, industrial plants that manufacture hydrofluoric acid, metal extraction and mining, electric and electronic industries, phosphate fertilizer plants, textile dyeing, plastics factories and thermal power plants (Ayoob and Gupta, 2006;Yousefi et al, 2019).…”
Section: Sources Of Fluoride In the Study Areamentioning
confidence: 99%
“…1where I is the intake of contaminated water (mg kg -1 day -1 ), C is the concentration of metal in the water (mg L -1 ), IR is the water intake rate (L day -1 ), EF is the frequency of exposure (days year -1 ), ED is the average duration of exposure (year), BW is the average body weight of the subject during exposure (kg), and AT is the average period of exposure, in days. 35 The data regarding the water consumption of the population were obtained through questionnaires applied in the communities. Only the mean time at which contaminants may cause non-carcinogenic or systemic effects to human health, which includes miscellaneous conditions other than cancer or gene mutations, was considered.…”
Section: Toxicity Assessmentmentioning
confidence: 99%